Deterring Kickbacks and Encouraging Entry in Public Procurement Markets : Evidence from Firm Surveys in 88 Developing Countries - Knack, Stephen (World Bank, Washington, DC, 2017)
There is relatively little systematic evidence on the links between procurement systems and outcomes such as competition and corruption levels. This paper adds to the evidence base, using data on almost 34,000 firms from the World Bank’s Enterprise Surveys, in 88 countries that also have procurement systems data from Public Expenditure and Financial Accountability (PEFA) assessments. The analysis finds that in countries with more transparent procurement systems, where exceptions to open competition in tendering must be explicitly justified, firms are more likely to participate in public procurement markets. Moreover, firms report paying fewer and smaller kickbacks to officials in countries with more transparent procurement systems, effective and independent complaint mechanisms, and more effective external auditing systems. These findings—particularly on kickbacks—are robust to the inclusion of many controls and to a range of sensitivity tests. The study finds evidence that better procurement systems matter more for smaller firms’ participation in procurement markets and payment of kickbacks to obtain contracts, consistent with the view that information and transactions costs that are incurred in learning about bidding opportunities and fulfilling bidding requirements are more onerous for smaller firms. Falsification tests show that other, non-procurement indicators from the PEFA assessments are not associated with procurement outcomes, and that the PEFA procurement indicators are not strongly associated with other “governance”-related outcomes in firm surveys that are unrelated to procurement.